Pengembangan Strategi Pemasaran Coffee Shop Salapan Djati - Agung Prabowo, Vetto; Patria, Vigar; Pertiwi Hari sandi, Santi; Epty Hidayaty, Dwi (Jurnal Etnik: Ekonomi-Teknik, 2023)
This study aims to analyze and develop an effective marketing strategy system at the "Salapan Djati" coffee shop to increase competitiveness and business growth. Through a qualitative approach with the case study method, data were collected through in-depth interviews, direct observation, and analysis of documentation related to coffee marketing strategies. The results of the study show that "Salapan Djati" can improve the marketing strategy system through several main strategies: (1) developing innovative and quality coffee products, (2) appropriate market segmentation to target potential consumers, (3) utilization of social media and digital platforms in marketing campaigns, (4) improving the quality of customer service, and (5) cooperating with local suppliers to support sustainability and community aspects. The practical implication of this research is to provide guidance for coffee shop owners in designing and implementing an effective marketing strategy system to improve business performance.